Home Room Technique Group Guidance to Improve Student's Confidence - Durrotunnisa; Ni Putu Lianasari; Diah Utaminingsih (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The main problem in this study is the low self-confidence of students which is characterized by feelings of shame when they will argue in front of friends in a group atmosphere. The research participants were six students of SMP Negeri 3 Palu, and questionnaires on student self-confidence as the instrument. The collected data were analyzed descriptively and inferentially using the Wilcoxon sign rank test formula. The descriptive analysis revealed that five students had low self-confidence before attending group guidance with the home room technique, while one student had moderate self-confidence. There was an increase in students' self-confidence after attending group guidance services with the home room technique, with five students having moderate self-confidence and one having high self-confidence. The inferential analysis revealed a significant difference in student self-confidence before and after receiving the home room technique group guidance service.